Governance and the value relevance of tax avoidance / Akmalia M. Ariff and Hafiza A. Hashim - M. Ariff, Akmalia; A. Hashim, Hafiza (Accounting Research Institute & Faculty of Accountancy, 2014)
This paper provides evidence on the link amongst governance, tax avoidance and firm value. We examine whether tax avoidance is associated with firm value and whether the strength of such relation is dependent on the quality of governance. We employ Effective Tax Rates (ETR) to measure tax avoidance and the Malaysia Corporate Governance (MCG) Index to rate firm-level governance. The findings rely on analysis of 203 firms that are listed in the MCG Index between 2009 and 2011. We find that tax avoidance is viewed by investors as a value-enhancing activity, and that the value relevance of tax avoidance is greater for firms with higher-quality governance.